Internet censorship detected in Turkey (Turkey) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Turkey. Data sourced from CensoredPlanet.
Censorship Incident ID: TR-2026-0110. Severity: critical. Confidence: 65%